1952
DOI: 10.1002/jsfa.2740030308
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of methylated carbohydrates and rhamnose as components of soil polysaccharides

Abstract: oils, fully saturated triglycerides do not occur in significant proportions unless the unsaturated acid content is below that (about 350/6) necessary to permit of each mixed triglyceride molecule containing one unsaturated acyl group. On this assumption tiger fat which contains about jI% unsaturated acids should not contain any trisaturated glycerides. But land-animal fats stand apart from this rule and many fats (ox, sheep etc.) show a much higher content of trisaturated glycerides. From the graph in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1954
1954
1974
1974

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Soil polysaccharides have been shown to contain simple sugars and sugar acids (Forsyth, 1950), sugar amines (Bremner,19 o), and methyclays can occur through any or all of the mechanisms so far discussed, oxygen atoms such as exist on the interlame P lar surfaces of montmorilgroups to neutralize the sur 7 ace charge of the clay may contribute to the lated sugars (Duff, 1952). Thus the adsorption of soil PO I ysaccharides by In g./Ioo g. dry clay.…”
Section: Discussionmentioning
confidence: 99%
“…Soil polysaccharides have been shown to contain simple sugars and sugar acids (Forsyth, 1950), sugar amines (Bremner,19 o), and methyclays can occur through any or all of the mechanisms so far discussed, oxygen atoms such as exist on the interlame P lar surfaces of montmorilgroups to neutralize the sur 7 ace charge of the clay may contribute to the lated sugars (Duff, 1952). Thus the adsorption of soil PO I ysaccharides by In g./Ioo g. dry clay.…”
Section: Discussionmentioning
confidence: 99%
“…Soil polysaccharides have been shown to contain simple sugars and sugar acids (Forsyth, 1950), sugar amines (Bremner,19 o), and methyclays can occur through any or all of the mechanisms so far discussed, oxygen atoms such as exist on the interlame P lar surfaces of montmorilgroups to neutralize the sur 7 ace charge of the clay may contribute to the lated sugars (Duff, 1952). Thus the adsorption of soil PO I ysaccharides by interesting to note that the magnitude of the adsorption is considerably greater than the adsorptions of fulvic and humic acids that have previously been reported Jung, 1943; Khan, 1950;1951).…”
Section: Discussionmentioning
confidence: 99%
“…They also found that alanine, glycine, aspartic acid, and glutamic acid were the predominant amino acids present. Incubation experiments: materials employed (Duff, 1952;Whistler and Kirby, 1956 Infrared analysis of the polysaccharide showed absorption characteristic of three types of structure; acidic polysaccharide, peptide, and polymerized phosphate.…”
Section: Characterization Of the Polysaccharide Materialsmentioning
confidence: 99%